Accounting anomalies and fundamental analysis: A review of recent research advances - Richardson, Scott; Tuna, İrem and Wysocki, Peter (Journal of Accounting and Economics, 2010)
We survey recent research in accounting anomalies and fundamental analysis. We use forecasting of future earnings and returns as our organizing framework and suggest a roadmap for research aiming to document the forecasting benefits of accounting information. We combine this with opinions from the academic and practitioner communities to critically evaluate key clusters of papers about accounting anomalies and fundamental analysis disseminated over the last decade. Finally, we provide a new analysis on how an ex ante and ex post treatment of risk and transaction costs affects the accrual and PEAD anomalies, and offer suggestions for future research.